Designing Strategies to Improve the Competitiveness of Special Economic Zones - Fauzi, Achmad; Huseini, Martani; Rahayu, Amy Yayuk Sri (Technium Social Sciences Journal, 2022)
The development of Special Economic Zones (SEZs) is a way for many countries to increase their economic growth and competitiveness. Indonesia has been one of the countries that has developed the SEZ model since 2009, although long before the economic zone model in other forms had been implemented. SEZ’s main activities currently cover the processing and tourism industries. However, the development of SEZs in Indonesia has not been entirely able to become a driving force for the economy to increase economic growth and regional and national competitiveness. This study aims to identify the determinants and design strategies that can improve the competitiveness of SEZs in Indonesia. The qualitative multiple-case study method was applied to answer the research problem. Focus Group Discussions, Group Interviews, in-depth interviews, and document studies were carried out to obtain data, then processed by compiling them into open coding, axial coding, and selective coding, and then identification, looking at the patterns formed and interpretation of the existing data using techniques cross-case synthesis analysis. There are six determinant factors in research findings: innovation, collaboration, human resources, governance, location, and incentives. Furthermore, these six factors become the basis for designing strategies to improve the competitiveness of SEZs in Indonesia.